International financial governance under stress : global structures versus national imperatives - Underhill, Geoffrey R. D. (2003)
Introduction : global market integration, financial crises and policy imperatives / Geoffrey R.D. Underhill and Xiaoke Zhang. - Reform of the international financial architecture : what has been written? / Jonathan Story. - Costs and benefits of financial globalisation : concepts, evidence and implications / John Williamson. - Capital controls : the neglected option / Benjamin J. Cohen. - Global structures and political imperatives : in search of normative underpinnings for international financial order / Geoffrey R.D. Underhill and Xiaoke Zhang. - Crisis consequences : lessons from Thailand / Pasuk Phongpaichit and Chris Baker. - The politics of financial reform : recapitalising Indonesia's banks / Richard Robison. - South Korea and the Asian crisis : the impact of the democratic deficit and OECD accession / Stephen L. Harris. - Currency crisis in Russia and other transition economies / Vladimir Popov. - Capital account convertibility and the national interest : has India got it right? / Vijay Joshi. - Learning to live without the Plan : financial reform in China / Shaun Breslin. - The Asian financial crisis and Japanese policy reactions / Masayuki Tadokoro. - Private capture, policy failures and financial crisis : evidence and lessons from South Korea and Thailand / Xiaoke Zhang and Geoffrey R.D. Underhill. - Governance, markets and power : the political economy of accounting reform in Indonesia / Andrew Rosser. - The private sector, international standards and the architecture of global finance / George Vojta and Marc Uzan. - The legitimacy of international organisations and the future of global governance / Jean-Marc Coicaud and Luiz A. Pereira Da Silka. - The G-7 and architecture debates : norms, authority and global financial governance / Andrew Baker. - Bail-outs, bail-ins, and bankruptcy : evolution of the new architecture / Manmohan S. Kumar and Marcus Miller. - Conclusion : towards the good governance of the international financial system / Geoffrey R.D. Underhill and Xiaoke Zhang